2014
DOI: 10.3389/fnins.2014.00152
|View full text |Cite
|
Sign up to set email alerts
|

Empathy and stress related neural responses in maternal decision making

Abstract: Mothers need to make caregiving decisions to meet the needs of children, which may or may not result in positive child feedback. Variations in caregivers' emotional reactivity to unpleasant child-feedback may be partially explained by their dispositional empathy levels. Furthermore, empathic response to the child's unpleasant feedback likely helps mothers to regulate their own stress. We investigated the relationship between maternal dispositional empathy, stress reactivity, and neural correlates of child feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 36 publications
6
90
0
Order By: Relevance
“…This is consistent with previous findings using baby cry and visual stimuli (Atzil et al, 2012;Ho et al, 2014;Kim et al, 2011;Phelps, 2004;Swain et al, 2008;Wittfoth-Schardt et al, 2012). …”
Section: Figure 2 About Here Please Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with previous findings using baby cry and visual stimuli (Atzil et al, 2012;Ho et al, 2014;Kim et al, 2011;Phelps, 2004;Swain et al, 2008;Wittfoth-Schardt et al, 2012). …”
Section: Figure 2 About Here Please Discussionsupporting
confidence: 93%
“…Women may use their close relationships with others in a different way to men: women may regulate their perception and responses to stress through the development of close affiliative bonds (Ho et al, 2014;Marazziti et al, 2006). In this way, plasma OT may be secreted in some women particularly under what they perceive to be stressful situations in order specifically to prompt a desire for affiliation (Taylor et al, 2006).…”
Section: Figure 2 About Here Please Discussionmentioning
confidence: 99%
“…Severity of postpartum depression was assessed on the 10-item Edinburgh Postnatal Depression Scale (EPDS; Cox et al, 1987) with reports of depressed mood, anhedonia, guilt, anxiety, and suicidal ideation experienced in the past 7 d rated on four-point scales (0 -3). An EPDS score above 12 indicates "probable" depression (Gibson et al, 2009). Mothers were considered to be breastfeeding if at least 80% of the infant's nutrition was delivered via breast milk.…”
Section: Methodsmentioning
confidence: 99%
“…This result is consistent with the "empathic decline" model, which is manifested by a decline in empathy values from the third year, preceded by an increase between the first and third years [15,16. ] This distribution has tried to be explained by attributing this decline to different factors: stress [18,19], and academic load 20, among others. However, there are studies that have observed that such decline has not been found in students of dentistry and medicine [1,3,6,13,14,21], which suggests that "decline" could be a particular case of different models of the behavior of empathy through the years [14].…”
Section: General Empathymentioning
confidence: 99%